Assessment of hand function after successful replantation of upper limb at arm - V. Koteswara Rao Rayidi; Venkata Bhargava Velde; Narsimha Rao; N Ram Babu; Laxman Sambari (Indian Journal of Plastic Surgery, 2016)
In upper arm replantation, a successful anastomosis guarantees the viability and good quality repair determines the overall function of the hand.There is paucity of successful arm replantation case reports in the literature. This is a case report of a successful arm replantation in a four year child with a near total functional outcome. We have used different scores to assess the functional outcome.